2021
DOI: 10.1093/rheumatology/keab638
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level and country-level socio-economic factors and health outcomes in spondyloarthritis: analysis of the ASAS-perSpA study

Abstract: Objectives To investigate the association between individual and country-level socioeconomic (SE) factors and health outcomes across spondyloarthritis (SpA) phenotypes. Methods Patients with axial SpA, peripheral SpA or psoriatic arthritis (PsA) from the ASAS-perSpA study (23 countries) were included. The effect of individual (age, gender, education and marital status) and country-level (e.g. Gross Domestic Product [GDP]) SE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…The median BASDAI score for our cohort was 2.2, which was slightly lower than that of other cohort studies and might limit the generalisability of the results, though other characteristics such as the proportion of males and HLA-B27 positivity were largely similar 80 81. Differences in the disease activity could be a reflection of country-level variation 82 83. Similarly, fewer patients in this study had possible anxiety as compared with other axSpA populations, which should be taken into consideration when interpreting results in other cohorts.…”
Section: Discussioncontrasting
confidence: 57%
“…The median BASDAI score for our cohort was 2.2, which was slightly lower than that of other cohort studies and might limit the generalisability of the results, though other characteristics such as the proportion of males and HLA-B27 positivity were largely similar 80 81. Differences in the disease activity could be a reflection of country-level variation 82 83. Similarly, fewer patients in this study had possible anxiety as compared with other axSpA populations, which should be taken into consideration when interpreting results in other cohorts.…”
Section: Discussioncontrasting
confidence: 57%
“…Our study showed that disease activity scores were higher in women over time as reflected by both ASDAS and BASDAI. This finding is in line with previous cross-sectional and observational studies reporting that female sex was associated with higher disease activity, mainly observed on the BASDAI scores (5)(6)(7)(8)10,13,25,26), and a few recent studies also reported higher ASDAS in women (12,28). In this study, women had more peripheral arthritis and enthesitis than men.…”
Section: Discussionsupporting
confidence: 93%
“…This study has some strengths and limitations. This longitudinal analysis of the impact of sex on disease outcomes in axial SpA brings different and valuable information compared to published data, which are mainly cross-sectional (5)(6)(7)(8)10,12,13,15,25,26). A strength of our study is the validated methodologies used to analyze longitudinal data: mixed-effects models and trajectory analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations